Healthy development in young children : evidence-based interventions for early education - Alfonso, Vincent C.; DuPaul, George J. (American Psychological Association, 2020)
"Every year brings new research studies that aim to describe early childhood development. Despite this boom in research, there has been little useful translation of these studies into clear recommendations for educators and mental health practitioners. This book shows experienced educators and mental health practitioners who work with young children (2 5 years of age) how to implement programs and interventions based on the latest scientific research in day care centers, preschools, special education settings, and kindergartens. Chapters in this volume offer guidelines on child assessment across five key areas of development-cognitive, language, behavioral and social emotional functioning, adaptive behavior, and motor skills. Contributors describe interventions to help children meet age appropriate expectations regarding cognitive and emotional maturity, and other key developmental tasks including numerical understanding, early literacy programs; and play. Other chapters discuss broad policies and legal issues impacting early education. Special attention is given to interventions for preschoolers with developmental disabilities, and the unique needs of children who are culturally and linguistically diverse. Psychologists, speech language pathologists, social workers, and teachers will find a wealth of information in this comprehensive, practical volume"--